Research subject advocacy: program implementation and evaluation at clinical and translational science award centers - Kost, Rhonda G; Reider, Carson; Stephens, Julie; Schuff, Kathryn G (Academic medicine, 2012)
In 2000, the National Center for Research Resources mandated that general research centers create a research subject advocate (RSA) position. In 2008, the Clinical and Translational Science Award (CTSA) consortium endorsed a new advocacy model based on four RSA Best Practice Functions. The authors surveyed CTSA centers to learn about their implementation of programs to fulfill the RSA functions. In 2010, the RSA taskforce developed a two-part online survey to examine leadership, organizational structure, governance, scope, collaboration and integration, and funding and evaluation of RSA activities implemented at CTSA centers. Respondents from 45 RSA programs at 43 CTSA centers completed the survey. Senior university or CTSA officials led all programs. Ninety-six percent (43/45) of programs were funded by a CTSA core. Eighty percent (36/45) designated an individual "RSA." Ninety-eight percent (44/45) provided diverse services either in collaboration with or complementary to other departments, including development of data and safety monitoring plans (16/45; 36%), informed consent observation (10/45; 22%), training responsive to audit findings (12/45; 27%), and direct advocacy services to participants (11/45; 24%). Eighty-six percent (24/28) reported qualitative evaluation methods for these activities. RSA programs conduct both collaborative and unique research protection activities. This survey, an initial step in developing a more robust mechanism for evaluating RSA programs, collected valuable feedback. The authors recommend defining and developing outcome-based evaluation measures that take the heterogeneity of the individual RSA programs into account while advancing their value and effectiveness in protecting human research subject participants.